2023
DOI: 10.1007/s43657-023-00098-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Phenotypes of Alzheimer’s Disease: Mechanisms and Potential Therapy

Abstract: Years of intensive research has brought us extensive knowledge on the genetic and molecular factors involved in Alzheimer's disease (AD). In addition to the mutations in the three main causative genes of familial AD (FAD) including presenilins and amyloid precursor protein genes, studies have identified several genes as the most plausible genes for the onset and progression of FAD, such as triggering receptor expressed on myeloid cells 2, sortilin-related receptor 1, and adenosine triphosphate-binding cassette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 192 publications
0
8
0
Order By: Relevance
“…The majority of AD cases are sporadic, but it is affected by several genes. Of the genetic variants that are known to cause the AD include presenilin 1 (PSEN1), presenilin 2 (PSEN2), and amyloid precursor protein (APP) [128]. The Apolipoprotein E (APOE) ε4 allele is reported to be the strongest genetic risk factor for SAD [129].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of AD cases are sporadic, but it is affected by several genes. Of the genetic variants that are known to cause the AD include presenilin 1 (PSEN1), presenilin 2 (PSEN2), and amyloid precursor protein (APP) [128]. The Apolipoprotein E (APOE) ε4 allele is reported to be the strongest genetic risk factor for SAD [129].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The Apolipoprotein E (APOE) ε4 allele is reported to be the strongest genetic risk factor for SAD [129]. Additionally, other contributing loci that affect AD include triggering receptors expressed on myeloid cells 2 (TREM2), sortilin-related receptor 1 (SORL1), and adenosine triphosphate-binding cassette transporter subfamily A member 7 (ABCA7) [128,130,131]. Similar to AD, genetic factors also increase the risk for the development of Parkinson's disease (PD).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Apolipoprotein E ( APOE ) gene variants follow next, as one copy of the ε4 allele can increase the risk of developing AD by 2–6 times, while two copies increase the risk by 7–21 times. Genetic studies have identified many other AD susceptibility loci and a large number of rare variants associated to AD (e.g., TREM 2, SORL1, ABCA7) [ 3 , 5 , 6 , 7 ]. Moreover, environmental factors (e.g., heavy metals, pesticides), comorbidities (e.g., diabetes, traumatic brain injury) and lifestyle (e.g., smoking, high-fat diet) can impact AD risk [ 5 , 8 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Most researchers suggest that AD may be associated with the accumulation of beta-amyloid and the formation of neurofibrillary tangles in the cerebral cortex and subcortical gray matter [21,[35][36][37]. Specific cases of the disease have been associated with mutations in the amyloid precursor protein gene, in the presenilin genes and some others [38][39][40][41]. Additionally, the presence of the ε4 allele of the APOE gene has found to be significant.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%